Auditory frequency discrimination in children with Specific Language Impairment: a longitudinal study - P. R. Hill; J. H. Hogben; D. V. M. Bishop (2005)
It has been proposed that specific language impairment (SLI) is caused by an impairment of auditory processing, but it is unclear whether this problem affects temporal processing, frequency discrimination (FD), or both. Furthermore, there are few longitudinal studies in this area, making it hard to establish whether any deficit represents a developmental lag or a more permanent deficit. To address these issues, the authors retested a group of 10 children with SLI and 12 control children first tested 42 months previously. At Time 1, the children with SLI (between 9 and 12 years of age) had significantly elevated FD thresholds compared to the matched controls. At Time 2, the thresholds of both groups had improved, but the children with SLI still had poorer FD thresholds than those of the controls. To assess temporal resolution, auditory backward masking was measured and it was found that most of the children with SLI performed as well as the controls, but 2 children had exceptionally high thresholds. There was also greater variability among the children with SLI compared to that measured among the controls on the FD task. These studies indicate considerable heterogeneity in auditory function among children with SLI and suggest that, as with auditory temporal deficits, difficulties in FD discrimination are important in this population.